Flow regime identification in horizontal pneumatic conveying by nonintrusive acoustic emission detection. Issue 5 (19th February 2019) - Zhang, Peng; Tian, Sihang; Yang, Yao; Huang, Zhengliang; Sun, Jingyuan; Liao, Zuwei; Jiang, Binbo; Wang, Jingdai; Yang, Yongrong; Xie, Lei; Su, Hongye
Abstract: This work investigated flow regimes identification in horizontal pneumatic conveying from the scope of particle motions based on acoustic emission detection. Results showed that the variation of acoustic energy and acoustic energy fraction could be used to identify the transition between suspension flow and stratified flow. Near the transition point, the acoustic energy was maximum, and the energy fraction of particle‐wall collision mutated at high mass fluxes. Furthermore, the fluctuation distribution index (FI) was constructed learning from the concept of polymer molecular weight distribution index, and the "circumferential fluctuation difference (D)" was defined. Based on this, new identification criteria and flow regime diagram were established. In suspension flow, D >0. In stratified flow, D <0. While in slug flow, D ≈ 0. According to these criteria, flow regimes can be identified independently of changing trends of measurement parameters. The universality of above criteria was further verified under different operating conditions.